Sub-Antarctic plant-soil interactions in a changing world: plant N acquisition and growth under warming on Marion Island - Pallett, Nita (Department of Biological Sciences, 2024)
It is widely accepted that in cold ecosystems, strong abiotic (e.g., temperature) controls over soil decomposition processes result in N-limited plant productivity and soils replete in organic N (oN, e.g., amino acids) but not inorganic N (iN, i.e., NH4 + and NO3 - ). Recent advances in our understanding of plant N use have shown that cold ecosystem plants meet the bulk of their N requirements through direct oN acquisition. Climate warming in cold ecosystems under global change is expected to alleviate the temperature limitations to soil decomposition, effectively increasing N-availability through iN release. This has resulted in predictions for stronger indirect than direct effects on plant productivity. Additionally, increasing iN fractions may affect coldecosystem plant nutrition by altering the N-form predominantly acquired from oN to iN. Investigations into plant oN acquisition and the effects of soil warming on plant productivity are largely restricted to northern high latitudes, leaving southern cold ecosystems such as the subAntarctic underrepresented. Sub-Antarctic soils are typically replete in oN but not iN, however, plant oN uptake has not been accounted for in terrestrial N-budgets. Furthermore, the islands are experiencing high rates of climate change including increasing temperatures. This thesis examines sub-Antarctic plant-soil interactions, investigating whether sub-Antarctic grasses acquire oN and how soil warming affects plant growth and nutrition. Potted and field experiments were run with four common grasses (Polypogon magellanicus, Poa cookii, Agrostis stolonifera, and Poa annua) from sub-Antarctic Marion Island (MI, -46.9, 37.8). I hypothesised that sub-Antarctic grasses acquire oN which affects plant growth relative to iN and that soil warming influences plant growth directly and indirectly through stimulating microbial iN mineralisation and plant nutrition by altering bioavailable oN and iN soil fractions. Grasses supplied with either 15N-enriched oN (glycine) or iN (NO3 - ) provided evidence for oN acquisition in hydroponics. Experimental oN and iN provision (in hydroponics) resulted in higher relative growth rates (RGR) on iN compared to oN, but species-specific differences in biomass allocation under the different N-forms and [N]. Grasses supplied with 15N-glycine in situ resulted in significant 15N enrichment, although intact oN acquisition in situ cannot be determined with the use of only 15N-labelled glycine. Considering the high [oN] in MI soils, this evidence suggests that oN represents an important N-resource for sub-Antarctic vegetation. A five-month warming experiment (MI ambient summer temperatures +3°C) resulted in limited biomass increases, which was only significant (p < 0.05) for P. annua (by 42%), and soil NH4 + increased by 12%. A fertilisation (NPK) treatment resulted in substantially higher plant biomass increases than warming (449% relative to 24%, respectively), suggesting that warming-induced N-release should not be assumed to strongly stimulate plant biomass. Soil warming did not influence plant acquisition of oN or iN. A soil incubation experiment (42 d; 5°C control, +3°C and +6°C warming) showed no effect of warming on soil iN, oN, or PO4 3- , although iN increased and PO4 3- decreased with increasing total organic C (TOC). Microbial biomass (C) increased with soil TOC but was not affected by warming. While microbial P increased with TOC and the +6°C warming treatment, microbial N was unaffected by warming and did not change with TOC. These results highlight the importance of investigating prevailing assumptions on soil-plant processes in cold ecosystems, including outdated assumptions that subAntarctic grasses only acquire iN, and that warming-induced N-release strongly stimulates plant productivity. The evidence presented here suggests that early work on MI underestimated total plant-available N, thus the sub-Antarctic terrestrial N-budget requires re-evaluation. Plant biomass and microbial mineralisation only showed limited or non-significant responses to soil warming, challenging the predictions for large, widespread effects of soil warming on N-release in cold ecosystems. The large differences in plant biomass under NPK relative to warming suggest that plant responses to increased N are limited if other nutrients, e.g., P, do not increase concomitantly. Despite strong temperature controls on cold-ecosystem soil decomposition rates, the stimulatory effects of short-term warming may be curtailed by a combination of interactive plant-soil processes.